Production technology of high-cleanliness gypsum board covering paper - LI WEI (2017)
The invention relates to a production technology of high-cleanliness gypsum board covering paper, and belongs to the technical field of gypsum board covering paper. The problem that the surface cleanliness of gypsum board covering paper in the prior art cannot meet the requirements is solved. The technology comprises the steps of pulping and papermaking, wherein pulping is divided into two production lines including a deinked pulp production line and an OCC production line; a surface layer net, a lining layer net, a core layer net and a bottom layer net are compounded and formed during papermaking. Clean enzyme, energy-gathering enzyme and talcum powder are added in a pulping section, the cost is reduced, and the whiteness and smoothness of the paper are improved. 种高洁净度石膏板护面纸的生产工艺，属于石膏板护面纸技术领域，现有技术石膏板护面纸表面洁净度无法满足要求的问题，包括制浆和造纸，制浆分为两条生产线：脱墨浆生产线和OCC生产线，造纸，采用面、衬、芯、底四层网复合成型。其中，在制浆工段中加入洁净酶、聚能酶和滑石粉，本发明节约了成本，提供了纸张的白度和光滑度。